Nursing students' experiences of communication in a multilingual and multicultural clinical environment: A qualitative study - Daniel Opotamutale Ashipala; Maujarukua Matundu (Wiley, 2023)
Abstract Aim The aim of this study was to investigate nursing students' experiences of communication in a multilingual and multicultural clinical environment. Background Effective communication in a healthcare setting plays a crucial role in patient care. Yet, since universities, globally, have experienced an increase in the enrolment of both local and international students in various degree programmes, student populations have become increasingly multilingual and multicultural. This study was conducted in a multilingual country where many languages are not spoken by all citizens, which results in nursing students experiencing varied outcomes. Design A qualitative, explorative, descriptive research design was used. Methods Sixteen nursing students enrolled in either the Bachelor of Nursing Science (Clinical, Honours) or the Diploma in Nursing Science. Data were collected by means of in‐depth, semi‐structured interviews with a sample of 16 nursing students who were selected through convenience sampling. Data were analysed using thematic analysis. Results The study revealed four themes: aspects that complicate communication; interesting aspects about communication; the need for communication assistance; and the need for policy intervention, which is key to addressing challenges in multilingual clinical environments.